Família multiespécie: análise da (in)viabilidade de tutelar judicialmente questões de guarda, ajuda de custos e convivência de animais de estimação em face de divórcio ou dissolução de união estável - Posser, Juliana Pastre (2024)
The study of the (in)feasibility of judicially protecting issues relating to pets is justified given the visible changes that have occurred in the field of Family Law, with an increasing emphasis on jurisprudence. In effect, it is possible to analyze – even if timidly – ​​the growing number of demands in the Judiciary to resolve issues involving sentient animals. There is a gap in the legislation, since, for occasion of the Civil Code of 2002, there is no legal provision to resolve disputes between people involving the relationship with the animal and the purpose of offering affection, friendship and affection, and not having it as an asset. Given this, the judge has decided in the light of analogy, customs and general principles of law aiming at resolving conflicts within divorce processes or dissolution of a stable union. Thus, with this possibility of application – as stipulated in article 4 of the Law of Introduction to the Standards of Brazilian Law (LINDB) – is carried out It is necessary to analyze the implications and viability, negative or positive, that may arise from this, culminating in new legislation covering such social transformations.